A modeling study on developing the condensing-frosting performance maps for a variable speed air source heat pump. (15th October 2022) - Liu, Shengnan; Bai, Xiaoxia; Deng, Shiming; Zhang, Long; Wei, Minchen
Abstract: For a variable speed (VS) space heating air source heat pump (ASHP) unit, to comprehensive study its frosting suppression and heating performances, a condensing-frosting performance map has been proposed. An experimental study using an experimental VS ASHP unit to obtain condensing-frosting performance maps was previously reported. However, obtaining such performance maps experimentally was time consuming and costly, and it was therefore considered highly necessary to develop a mathematical model to obtain performance maps through modeling study. In this paper, therefore, a mathematical model for the experimental VS ASHP unit was firstly developed by referring to previously published mathematical models for VS air conditioners. The developed model was experimentally validated using reported experimental data. The average relative errors between the measured and predicted total output heating capacity and COP were at 3.7% and 3.6%, respectively, and the average error between the measured and predicted outdoor coil surface temperature was at 0.2 °C. A follow-up modeling study was then carried out using the validated model to obtain condensing-frosting performance maps for the experimental VS ASHP unit having different outdoor coil surface areas and at different outdoor operating conditions. The modeling study results suggested that by increasing outdoor coil surface area of the experimental VS ASHP unit from 50% to 150%, its surface temperature on average was increased by more than 1.37 °C, which was inducive to a better frost suppression performance, and the total output heating capacity by more than 11.07%, but at a higher initial manufacturing cost. The modeling study results also indicated that the developed model can be a useful tool in studying the characteristics of VS ASHPs during both frosting and frost-free operations, which was important for guiding the design and control of ASHPs for their efficient and reliable operations. Graphical abstract: Image 1 Highlights: A model for a variable speed air source heat pump unit is developed and validated. Performance maps with heating capacity and outdoor coil temperature are proposed. Quantitative impact of outdoor coil surface area on system performance is clarified. Maximum frost-free heating capacities and COP at different conditions are obtained.